Synthesis, Linear, and Nonlinear Optical Characteristics of Schiff Base N’,2-Bis((E)-4-Hydroxy-3-Methoxybenzylidene)Hydrazine-1-Carbohydrazide: Experimental and Computational Study - C. Deepa; E. David; A. G. Bharathi Dileepan; S. Jeyaram (Journal of Fluorescence, 2026)

Marine heatwaves alter shell microbiomes and denitrification capacity: An oyster family-specific response - Giulia Filippini; Ana B. Bugnot; Wayne O'Connor; Paul E. Gribben; Deepa R. Varkey; Ian T. Paulsen; Katherine A. Dafforn (Marine Pollution Bulletin, 2026)

Bringing the Teaching Close to Home: Implementation of a Near-Peer Model for Introductory Hematology-Oncology Fellowship Lecture Series - Jonathan L. Berry; Lauren O’Loughlin; Anthony Iacoviello; Kevin Barnum; Barbara D. Lam; Matthew Chase; Reed E. Drews; Jason A. Freed; Rushad Patell; Deepa Rangachari (Journal of Cancer Education, 2026)

Cryopreservation of bael (Aegle marmelos L.Corr.) using encapsulated axillary buds - E. Deepa; Deepa S. Nair; Swapna Alex; K. B. Soni; M. M. Viji; B. Parvathi (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Low-resolution sodium NMR in food biopolymers: The accessible information - Diane Neagu; Deepa Agarwal; Charfedinne Ayed; Timothy B. Benson; William MacNaughtan; Sandra E. Hill (Journal of Food Engineering, 2025)

The influence of bioturbator activity on sediment bacterial structure and function is moderated by environment - Julia Palmer; Ana B. Bugnot; Giulia Filippini; Paul E. Gribben; Deepa Varkey; Katherine Erickson; Katherine A. Dafforn (Marine Environmental Research, 2024)

Using a multi-scale approach to examine the effects of field margins and landscape features on predatory carabid communities in crop fields - Kelly Jowett; Alice E. Milne; Dion Garrett; Dan Blumgart; Simon G. Potts; Deepa Senapathi; Jonathan Storkey (Agriculture, Ecosystems & Environment, 2024)

Above and below-ground bacterial communities shift in seagrass beds with warmer temperatures - Luke DA. Walker; Paul E. Gribben; Tim M. Glasby; Ezequiel M. Marzinelli; Deepa R. Varkey; Katherine A. Dafforn (Frontiers in Marine Science, 2024)
Current rates of ocean warming are predicted to exacerbate ongoing declines in seagrass populations. Above-ground responses of seagrass to increasing temperatures have been studied from a direct physiological perspective while indirect effects, including changes to microbially-mediated below-ground processes, remain poorly understood. To test potential effects of increased temperature on seagrass growth and associated microbial communities, we sampled seagrass beds experiencing ambient and elevated water temperatures at Lake Macquarie, Australia. Sites with warmer water were associated with a plume from a power station discharge channel with temperatures analogous to conditions predicted by 2100 under current rates of ocean warming (+3°C). The microbial community composition in both sediments and leaf tissues varied significantly between warm and ambient water temperatures with higher relative abundances of putative sulphate-reducing bacteria such as Desulfocapsaceae, Desulfobulbaceae and Desulfosarcinaceae in sedimentary communities in warm water. Above-ground biomass and seagrass growth rates were greater at warm sites while below-ground biomass and detrital decomposition rates showed no difference suggesting potential buffering of temperature effects below-ground. These findings suggest a 3°C rise in temperate regions is unlikely to induce mortality in seagrass however, it may shift microbial communities towards more homogenous structure and composition.

Nitrogen-cycling genes in oyster reefs and surrounding sediments: Relationships with environmental factors and respective nitrogen rates - Giulia Filippini; Ana B. Bugnot; Deepa R. Varkey; Nachshon Siboni; Angus Ferguson; Paul E. Gribben; Katherine Erickson; Julia Palmer; Katherine A. Dafforn (Marine Pollution Bulletin, 2023)

A multicentre evaluation and expert recommendations of use of the newly developed BioFire Joint Infection polymerase chain reaction panel - Kordo Saeed; Nusreen Ahmad-Saeed; Rachel Annett; Gavin Barlow; Lucinda Barrett; Sara E. Boyd; Nicola Boran; Peter Davies; Harriet Hughes; Gwennan Jones; Laura Leach; Maureen Lynch; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Septic arthritis is a serious condition with significant morbidity and mortality, routinely diagnosed using culture. The FDA has recently approved the rapid molecular BioFire® Joint Infection Panel (BJIP) for synovial fluid. We aimed to evaluate the BJIP compared to culture and its potential use in patient management. A multicentre retrospective evaluation of BJIP was conducted in the UK and Ireland. Positive percent agreement (PPA) and negative percent agreement (NPA) were calculated between the BJIP and routine culture. A multidisciplinary team (MDT) discussion addressing the optimal or potential case use of the assay practice was facilitated. Three hundred ninety-nine surplus synovial fluid samples (~ 70% from native joints) from eight centres were processed using BJIP in addition to routine culture. An increased yield of positive results was detected using BJIP compared to routine culture (98 vs 83), giving an overall PPA of 91.6% and overall NPA of 93% for the BJIP compared to culture results. The BJIP detected resistant markers and additional organisms that could influence antibiotic choices including Neisseria gonorrhoeae and Kingella kingae . The MDT agreed that the assay could be used, in addition to standard methods, in adult and children patients with specialist advice use based on local needs. Rapid results from BJIP were assessed as having potential clinical impact on patient management. Organisms not included in the panel may be clinically significant and may limit the value of this test for PJI.

Moths and butterflies on alien shores: Global biogeography of non‐native Lepidoptera - Richard Mally; Rebecca M. Turner; Rachael E. Blake; Gyda Fenn‐Moltu; Cleo Bertelsmeier; Eckehard G. Brockerhoff; Robert J. B. Hoare; Helen F. Nahrung; Alain Roques; Deepa S. Pureswaran; Takehiko Yamanaka; Andrew M. Liebhold (Journal of Biogeography, 2022)
Aim Lepidoptera is a highly diverse, predominantly herbivorous insect order, with species transported to outside their native range largely facilitated by the global trade of plants and plant‐based goods. Analogous to island disharmony, we examine invasion disharmony, where species filtering during invasions increases systematic compositional differences between native and non‐native species assemblages, and test whether some families are more successful at establishing in non‐native regions than others. Location Hawaii, North America, Galapagos, Europe, South Africa, South Korea, Japan, Nansei Islands, Ogasawara Islands, Australia, New Zealand. Taxon Lepidoptera. Methods We compared numbers of non‐native, unintentionally introduced Lepidoptera species with the land area of 11 regions worldwide. Differences among native and non‐native assemblages in the distribution of species among families were investigated using ordination analysis. We tested whether invasion disharmony is explained by propagule pressure (proxied by species richness in border interceptions) and if families were associated with specific trade commodities. Results In total, 741 non‐native Lepidoptera species, accounting for 0.47% of the global diversity of lepidopterans, are established in at least one of the 11 regions. Crambidae, Pyralidae, Tineidae and Gracillariidae were particularly successful invaders, whereas the two most species‐rich families, Erebidae and Geometridae, were under‐represented among non‐native Lepidoptera. Much of the variation in species numbers in the native, and less so in the non‐native assemblages could be attributed to land area. Although native assemblages were similar among nearby regions, non‐native assemblages were not, suggesting geography had little effect on invasion disharmony. Comparison of established with intercepted species revealed that macromoth families were generally under‐represented in establishments, whereas several micromoth families were under‐represented in interceptions. This discrepancy may relate to greater detectability of larger species or high propagule pressure via associations with specific invasion pathways. Main conclusions Invasion disharmony in Lepidoptera appears to be driven by processes unrelated to the success of native assemblages. While native assemblages developed through long‐term evolutionary radiation, the composition of non‐native assemblages is driven by differential invasion pathways and traits affecting the establishment of founder populations that vary among families.

Assessment of Spatial and Temporal Changes in Water Quality of a Tropical River in Southern Western Ghats, Kerala, India, Using Physicochemical Quality Indices and Multivariate Analysis - Ajoy Saha; T. T. Paul; Deepa Sudheesan; Sravan Kumar Sharma; V. R. Suresh; B. K. Das; S. Manoharan; M. E. Vijaykumar; S. Samanta; Chayna Jana (Natural Resources Research, 2022)

The role of climate in past forest loss in an ecologically important region of South Asia - Alice E. Haughan; Nathalie Pettorelli; Simon G. Potts; Deepa Senapathi (Global Change Biology, 2022)
Tropical forests in India have declined at an alarming rate over the past century, with extensive literature focusing on the high contributions of agricultural expansions to deforestation, while the effects of climate change have largely been overlooked. Climate change effects, such as increasing temperatures, drought and flooding, have already occurred, and are projected to worsen. Climate velocity, a metric that accounts for spatial heterogeneity in climate, can help identify contiguous areas under greater climate stress and potential climate refuges in addition to traditional temporal trends. Here, we examined the relative contribution of climate changes to forest loss within an area of India, Jammu, Kashmir, and Ladakh during the period 2001–2018, at two spatial (regional and study area) and two temporal (seasonal and annual) scales. This includes, for the first time, a characterization of climate velocity in the area. Our findings show that annual forest loss increased substantially over the 17‐year period examined (2001–2018), with the majority of forest loss occurring in the Northeast region. Decreases in temporal trends of temperature and precipitation were most associated with forest losses, but there was large spatial and seasonal variation in the relationship. In every region except the Northeast, forest losses were correlated with faster velocities of at least one climate variable but overlapping areas of high velocities were rare. Our findings indicate that climate changes have played an important role in past forest loss within the study area but likely remain secondary to other factors at present. We stress concern for climates velocities recorded reaching 97 km year −1 , and highlight that understanding the different regional and seasonal relationships between climatic conditions and forest distributions will be key to effective protection of the area's remaining forests as climate change accelerates.

Investigation of Kinetic Drug Release Characteristics and In Vitro Evaluation of Sustained-Release Matrix Tablets of a Selective COX-2 Inhibitor for Rheumatic Diseases - M. Karthikeyan; M. K. Deepa; E. Bassim; C. S. Rahna; K. R. Sree Raj (Journal of Pharmaceutical Innovation, 2021)

Single-Turnover Variable Chlorophyll Fluorescence as a Tool for Assessing Phytoplankton Photosynthesis and Primary Productivity: Opportunities, Caveats and Recommendations - Nina Schuback; Philippe D. Tortell; Ilana Berman-Frank; Douglas A. Campbell; Aurea Ciotti; Emilie Courtecuisse; Zachary K. Erickson; Tetsuichi Fujiki; Kimberly Halsey; Anna E. Hickman; Yannick Huot; Maxime Y. Gorbunov; et al. (Frontiers in Marine Science, 2021)
Phytoplankton photosynthetic physiology can be investigated through single-turnover variable chlorophyll fluorescence (ST-ChlF) approaches, which carry unique potential to autonomously collect data at high spatial and temporal resolution. Over the past decades, significant progress has been made in the development and application of ST-ChlF methods in aquatic ecosystems, and in the interpretation of the resulting observations. At the same time, however, an increasing number of sensor types, sampling protocols, and data processing algorithms have created confusion and uncertainty among potential users, with a growing divergence of practice among different research groups. In this review, we assist the existing and upcoming user community by providing an overview of current approaches and consensus recommendations for the use of ST-ChlF measurements to examine in-situ phytoplankton productivity and photo-physiology. We argue that a consistency of practice and adherence to basic operational and quality control standards is critical to ensuring data inter-comparability. Large datasets of inter-comparable and globally coherent ST-ChlF observations hold the potential to reveal large-scale patterns and trends in phytoplankton photo-physiology, photosynthetic rates and bottom-up controls on primary productivity. As such, they hold great potential to provide invaluable physiological observations on the scales relevant for the development and validation of ecosystem models and remote sensing algorithms.

Complete Genome Sequence of Penicillium oxalicum Strain SGAir0226 Isolated from Outdoor Tropical Air in Singapore - Anjali Bansal Gupta; Nicolas E. Gaultier; Ngu War Aung; Rikky W. Purbojati; Elaine L. Oliveira; Anthony Wong; Deepa Panicker; Alexander Putra; Akira Uchida; Daniela I. Drautz-Moses; Stephan C. Schuster (Mycopathologia, 2020)

Accelerated decline in cognition in a mouse model of increased oxidative stress - Sreemathi Logan; Gordon H. Royce; Daniel Owen; Julie Farley; Michelle Ranjo-Bishop; William E. Sonntag; Sathyaseelan S. Deepa (GeroScience, 2019)

Genetic mapping of the European canker (Neonectria ditissima) resistance locus Rnd1 from Malus ‘Robusta 5’ - Vincent G. M. Bus; Reiny W. A. Scheper; Monika Walter; Rebecca E. Campbell; Biff Kitson; Lauren Turner; Brent M. Fisher; Sarah L. Johnston; Chen Wu; Cecilia H. Deng; Gagandeep Singla; Deepa Bowatte; et al. (Tree Genetics & Genomes, 2019)

Comparative Transcriptome Analysis of Two Species of Curcuma Contrasting in a High-Value Compound Curcumin: Insights into Genetic Basis and Regulation of Biosynthesis - T. E. Sheeja; K. Deepa; R. Santhi; B. Sasikumar (Plant Molecular Biology Reporter, 2015)

The effect of flavanol-rich cocoa on cerebral perfusion in healthy older adults during conscious resting state: a placebo controlled, crossover, acute trial - Daniel J. Lamport; Deepa Pal; Christina Moutsiana; David T. Field; Claire M. Williams; Jeremy P. E. Spencer; Laurie T. Butler (Psychopharmacology, 2015)

A simple and efficient protocol for isolation of high quality functional RNA from different tissues of turmeric (Curcuma longa L.) - K. Deepa; T. E. Sheeja; R. Santhi; B. Sasikumar; Anu Cyriac; P. V. Deepesh; D. Prasath (Physiology and Molecular Biology of Plants, 2014)

Accumulation of mercury and other heavy metals in edible fishes of Cochin backwaters, Southwest India - Mahesh Mohan; M. Deepa; E. V. Ramasamy; A. P. Thomas (Environmental Monitoring and Assessment, 2012)

Immunoregulation of a CB2 Receptor Agonist in a Murine Model of NeuroAIDS - Santhi Gorantla; Edward Makarov; Deepa Roy; Jennifer Finke-Dwyer; L. Charles Murrin; Howard E. Gendelman; Larisa Poluektova (Journal of Neuroimmune Pharmacology, 2010)

Genome mapping of an apple scab, a powdery mildew and a woolly apple aphid resistance gene from open-pollinated Mildew Immune Selection - Vincent G. M. Bus; Heather C. M. Bassett; Deepa Bowatte; David Chagné; Chandra A. Ranatunga; Dulantha Ulluwishewa; Claudia Wiedow; Susan E. Gardiner (Tree Genetics & Genomes, 2010)